How to ski faster: art or science? - Brodie, M.; Walmsley, A.; Page, W. (Science and Skiing IV, 2009)
INTRODUCTION: What makes one athlete fastest? Is it science or art? In this paper, the biomechanical analysis of an athlete's technique is used to address these questions. Humans have long been obsessed with the artistic appearance of an athletic performance; this "kinematic Obsession" can often obscure the underlying forces - the science of skilled human movement. The analysis shows that in ski racing, a turn that is considered most visually acceptable is not always the fastest turn. In addition, the fastest turn does not necessarily produce the winning Overall course time. Here underlies the art of global race strategy choice.